2018
DOI: 10.1097/icl.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hospital Cornea Retrieval and Voluntary Eye Donation Program in Eye Banking

Abstract: Most corneas retrieved through HCRP were of optical grade quality and efforts should be focused on HCRP to reduce the demand-supply deficit in cornea transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…6 NEB is in a favorable location, which is an advantage for shorter tissue excision and preservation time. In our study, average DPT was 5.7 hrs (Figure 2), which is similar to that reported by Sharma et al 5 Other reports mentioned averageDPT of 2.8 to 3.9 hrs. 3,7,9 Cunningham et al 10 mentioned longer DPT of 18.5 hrs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6 NEB is in a favorable location, which is an advantage for shorter tissue excision and preservation time. In our study, average DPT was 5.7 hrs (Figure 2), which is similar to that reported by Sharma et al 5 Other reports mentioned averageDPT of 2.8 to 3.9 hrs. 3,7,9 Cunningham et al 10 mentioned longer DPT of 18.5 hrs.…”
Section: Discussionsupporting
confidence: 91%
“…The motivated collection of cornea in eye banks in various parts of India ranges from 69 to 86% which is similar to our studies. [3][4][5] Some eye banks in India rely mostly on home deaths with collections from 71 to 75.2% of the tissues. [6][7][8] In our study, all HCRP donors (87.7%) were within 10 kilometers of the eye bank (Table 1) unlike in the study of Desar et al, where the distance to travel to get corneas was more than 60 km in one third of the donors.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed younger donors were more from hospital donations. 4 A study by N Sharma et al reported in a HCRP-based study, which had a higher proportion of donors in younger age (H=81.6% vs. V=21%,) (H=Hospital, R=Residence). 9 A study done by Jonathan H. Lass et al showed that the corneas received from a donor 66 to 75 years old experienced cell loss of 79% at 10 yrs.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al 4 higher proportions of corneas in HCRP were used for optical indications 24.5% vs. 13.3%. While in a study by Patel et al, 11 cornea utilisation rate was as high as 79% with 68% of tissues received from coroners service and Oliva et al 6 found tissue utilisation as high as 72% in a Hospital Cornea Retrieval Program (HCRP) model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation